Lethal autonomous weapon systems and respect for human dignity - Kahn, Leonard (Frontiers in Big Data, 2022)
Much of the literature concerning the ethics of lethal autonomous weapons systems (LAWS) has focused on the idea of human dignity. The lion's share of that literature has been devoted to arguing that the use of LAWS is inconsistent with human dignity, so their use should be prohibited. Call this position “Prohibitionism.” Prohibitionists face several major obstacles. First, the concept of human dignity is itself a source of contention and difficult to operationalize. Second, Prohibitionists have struggled to form a consensus about a property P such that (i) all and only instances of LAWS have P and (ii) P is always inconsistent with human dignity. Third, an absolute ban on the use of LAWS seems implausible when they can be used on a limited basis for a good cause. Nevertheless, my main purpose here is to outline an alternative to Prohibitionism and recognize some of its advantages. This alternative, which I will call “Restrictionism,” recognizes the basic intuition at the heart of Prohibitionism - namely, that the use of LAWS raises a concern about human dignity. Moreover, it understands this concern to be rooted in the idea that LAWS can make determinations without human involvement about whom to target for lethal action. However, Restrictionism differs from Prohibitionism in several ways. First, it stipulates a basic standard for respecting human dignity. This basic standard is met by an action in a just war if and only if the action conforms with the following requirements: (i) the action is militarily necessary, (ii) the action involves a distinction between combatants and non-combatants, (iii) noncombatants are not targeted for harm, and (iv) any and all incidental harm to non-combatants is minimized. In short, the use of LAWS meets the standard of basic respect for human dignity if and only if it acts in a way that is functionally isomorphic with how a responsible combatant would act. This approach leaves open the question of whether and under what conditions LAWS can meet the standard of basic respect for human dignity.